PREVENTIVE MEASURES FOR URTICARIA, EARLY DIAGNOSIS AND IDENTIFICATION OF RISK FACTORS - BARNO H. ABDULLAEVA,; MUAZZAM U. ABDULLAJONOVA, (World Scientific Research Journal, 2025)
Abstract: Urticaria is a group of diseases characterized by the development of itchy wheals and/or angioedema [1]. In approximately 40% of cases, urticaria is accompanied by angioedema. The prevalence of acute urticaria ranges from 1 to 5% in the population, and among the pediatric population, the incidence of acute urticaria reaches 6.7%. According to recent estimates, 10 to 20% of the population will experience an episode of acute urticaria during their lifetime. About 50% of children with acute urticaria have concomitant allergic diseases [2]. According to S. Comert et al., the most common triggers of acute urticaria are drugs (38.1%), infections (35.2%), stress (24.7%) and food (17.8%) [5,7]. In another study, medications were also the most common cause of acute urticaria at 20.7%, followed by insect bites (10.2%) and food (7.4%) [3].